Modification of the Nuss procedure: The crossed bar technique for new subtypes of pectus excavatum - ERMERAK, NEZİH ONUR (My University, 2023)
BackgroundWe aim to describe four new subtypes of PE in detail and represent modification of the Nuss procedure called crossed bar technique for their optimum correction with good results.Methods101 patients who underwent crossed bar technique between August 2005 and February 2022 were included into the study.ResultsThe mean age of the patient series was 21.1 (range 15-38 years) years. Mean Haller index was 3.87. Mean operation duration was 86.84 min. 2 bars were used in 74 (73.3%) of the patients whereas 3 bars were preferred in 27 (26.7%) of them. Mean hospital stay was 4.1 (2-8) days, and all the patients were seen routinely on postoperative follow-up at 1st, 6th, and 18th months. Quality of life questionnaires revealed satisfaction.ConclusionsCross bar technique yields satisfactory results for these new subtypes and can be performed safely with good results in these selected group of patients.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Surgery Medicine Sciences; Health Sciences; KALP VE KALP DAMAR SİSTEMLERİ; Klinik Tıp; Klinik Tıp (MED); CERRAHİ; CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); SURGERY; Cerrahi; Kardiyoloji ve Kardiyovasküler Tıp; Surgery; Cardiology and Cardiovascular Medicine; Pectus excavatum; Nuss procedure; Minimally invasive repair; Chest wall deformities; Pectus carinatum; REPAIR; CLASSIFICATION; Pectus excavatum; Nuss procedure; Minimally invasive repair; Chest wall deformities; Pectus carinatum